The New Plan for the Prevention of School Failure in Catalonia (Spain) - Núria Llevot Calvet; Juan Agustín González Rodríguez; Alfonso Revilla Carrasco (LED Edizioni Universitarie, 2016)
This paper outlines the development of the Ministry of Education's Compensatory Education Program focusing on the changes in Catalonia due to the Plan for Language and Social Cohesion. This program was the emblematic result of the reformist policy adopted in 1983 in the field of education. It was, therefore, a hopeful and optimistic discourse aimed at correcting social inequalities and producing higher levels of social justice. Despite the inherent weaknesses of this approach, the Compensatory Education Program has enabled carrying out interventions in particularly complex areas and, in addition, the range of activities has been very broad and ambitious. Currently, its disappearance and transformation poses a challenge to the government to address the education of ethnic minorities at risk of social exclusion as well as actions to promote school success, to reduce school failure (scheduled for 2018). The development of Education's Compensatory Education Program will be useful to students of foreign origin in order to improve their academic opportunities and of continuing in the education system.